Optimizing LED lighting spectra for enhanced growth in controlled-environment vertical farms - H. Farhangi; V. Mozafari; H. R. Roosta; H. Shirani; S. Farhangi; M. Farhangi (Scientific Reports)
Abstract Due to growing demands for sustainable food production, controlled-environment vertical farms (CEVFs) have emerged as promising systems for cultivating vegetables and herbs in urban areas. However, these systems are often criticized for their high energy consumption, largely influenced by artificial lighting. This study aimed to optimize white LED-based lighting by supplementing it with additional deep red (DR, 660 nm) and far red (FR, 730 nm) light, evaluating effects on the growth of lettuce (Lactuca sativa cv. Batavia-Caipira) and basil (Ocimum basilicum cv. Emily). Five treatments were tested, all using a white LED base spectrum (with blue, green, and red components), with varying levels of DR and FR. In one treatment, light intensity (PPFD) was doubled to 244 µmol·m⁻2·s⁻1, while others were maintained at 122 µmol·m⁻2·s⁻1. The high-PPFD treatment resulted in the highest biomass, increasing fresh weight by 76% in lettuce and 79% in basil compared to white light alone. Among the treatments with equal PPFD, supplemental FR increased leaf number and canopy size, while DR enhanced biomass. Chlorophyll and nitrogen contents were highest under white-only light. Correlation analysis showed that the intensity of added DR and FR significantly influenced plant responses. These results suggest targeted DR and FR supplementation improves light-use efficiency in CEVFs.